A treatment effect method for merger analysis with an application to parking prices in Paris - Philippe Choné; Laurent Linnemer (Center for Economic Studies and ifo Institute (CESifo), 2010)
Most retrospective merger studies resort to the treatment effect approach, comparing the price dynamics in a treatment group and in a control group. We propose a systematic method to construct the groups, which applies to any industry with spatial competition. The method is consistent with the fact that mergers alter oligopolistic equilibria in complex ways, and thus that seemingly distant entities may be affected through indirect channels. An illustration based on a merger in the Parisian parking market is provided.
Keywords: L10; L40; 330; Fusion; Oligopol; Wirkungsanalyse; Ruhender Verkehr; Preis; Paris